Environmental policy mixes and target group heterogeneity: analysing Danish farmers' responses to the pesticide taxes. Issue 5 (2nd September 2020) - Pedersen, Anders Branth; Nielsen, Helle Ørsted; Daugbjerg, Carsten
ABSTRACT: In this article, we challenge two assumptions embedded in many ex-ante analyses of environmental policy instruments. Firstly, it is often assumed that target groups in environmental policy are homogeneous and thus can be expected to respond to policy instruments in a similar manner. Secondly, individual target group members are expected to respond to policy instruments like 'economic man', particularly in relation to MBIs applied in environmental policy. We argue that despite the 'behavioural turn' in public policy, the debate on policy instrument development and effectiveness has often neglected target group heterogeneity. E.g. members of a given policy target group may be driven by different motivations and each member may even act based on a combination of motivations. Target group heterogeneity suggests that rather than chasing a single perfect policy instrument, research and environmental governance should focus more on better policy mixes to match those differences in decision-making rationales. We argue that a focus on instrument combinations designed to effectively address policy problems where target groups are heterogeneous would mark a new and innovative stage in the research on policy instruments. We substantiate our argument by an empirical analysis of farmer responses to Danish agricultural pesticide taxes.